Early Christian ethics in interaction with Jewish and Greco-Roman contexts - Henten, J. W. van.; Verheyden, Jozef. (Studies in Theology and Religion, 2013)
Early Christian Ethics in Interaction with Jewish and Greco-Roman Contexts focuses upon the nexus of early Christian Ethics and its contexts as a dynamic process. The ongoing interaction with Jewish, Greco-Roman or early Christian traditions as well as with the social-historical context at large continuously transformed early Christian ethics. The volume proposes a dynamic model for studying culture and its various expressions in a society composed of several ethnic and religious groups. The contributions focus on specific transformations of ethics in key documents of early Christianity, or take a more comparative perspective pointing to similar developments and overlaps as well as particularities within early Christian writings, Hellenistic-Jewish writings, Dead Sea Scrolls and Jewish inscriptions.